Reconceptualization of Maslahah In Islamic Worship: Public Interest, State Policy, and Maqasid Al-Syari'ah - Andi Firmansyah; Achmad Musyahid; Lomba Sultan (Faculty of Law, Muhammadiyah University of Surabaya, 2024)
Human welfare encompasses personal well-being, social and communal interests, as well as national benefit. When a government aspires to build a strong nation and ensure a safe, peaceful, and orderly society, it must prioritize public interest over individual benefit. Likewise, individuals and communities seeking a harmonious and tranquil life should emphasize actions that generate greater collective benefit. Sharia, as a divinely ordered system of law, functions as a comprehensive guide for human life, aiming to realize welfare at both personal and social levels. In relation to the values ​​of maslahah embedded in the commands of worship, Islamic law affirms that all divine prescriptions are inherently beneficial and free from harm, even when they may appear unfavorable from a human perspective. Furthermore, the pursuit of benefit in safeguarding religion, life, intellect, lineage, and property constitutes a fundamental obligation within Islamic legal thought. These essentials, classified by Islamic scholars as indispensable necessities (darūriyyāt), if neglected, would result in severe harm to worldly and spiritual life, ultimately undermining human happiness, peace, and social stability.